Phy-chemical Attributes of Nano-scale V2O5/TiO2 Catalyst and Its’ Effect on Soot Oxidation - Deqing Mei; Lichang Li; Chen Zhu; Xiang Zhao; Yinnan Yuan (Bulletin of Chemical Reaction Engineering & Catalysis, 2016)
The V2O5 catalysts which supported on nano-scale TiO2 with variation of vanadium contents (5%, 10%, 20% and 40%) were prepared by an incipient-wetness impregnation method. The phase structures of nano-scale V2O5/TiO2 catalysts with different loading rates were characterized by Scanning electron microscope (SEM), X-Ray diffraction (XRD) and Fourier transform infrared (FT-IR) spectra. The oxidation activities of catalysts over diesel soot were performed in a themogravimetric analysis (TGA) system. The kinetics of the catalytic oxidation process were analyzed based on Flynn-Wall-Ozawa method. The characterization results showed that the phase structure of V2O5 supported on TiO2 depends heavily on the vanadium contents, which will put great effects on the catalytic performances for soot oxidation. At a low vanadium loading rates (V5-V20), active species exist as monomers and polymeric states. At a high loading rate (V40), the crystalline bulk V2O5 covers the surface of TiO2. The formed crystal structure occupied the active sites and led a decreasing in the catalytic effect. By comparing the characteristics temperatures of soot oxidation over V2O5 catalysts, the catalytic activities of catalysts with different loading rates for soot oxidation can be ranked as: V5 < V10 < V40 < V20. Via pyrolysis kinetics analysis, it is revealed that the activation energy of soot oxidation is minimum when the vanadium loading rates is 20%, which is fit well with the TG experimental results. The consistency of pyrolysis kinetics and TG experimental results confirm that the best activity catalyst is V20 in discussed catalysts of this paper, which is nearest to the monolayer dispersion saturated state of V2O5/TiO2 catalyst. Moreover, it convincingly demonstrate the obvious threshold effect in V2O5 catalysts.